Delayed puberty versus hypogonadism: a challenge for the pediatrician - Mauro Bozzola; Elena Bozzola; Chiara Montalbano; Filomena Andreina Stamati; Pietro Ferrara; Alberto Villani (Korean Society of Pediatric Endocrinology, 2018)
Constitutional delay of growth and puberty (CDGP) is the most common cause of delayed puberty (DP), is mainly found in males, and is characterized by short stature and delayed skeletal maturation. A family history of the subject comprising the timing of puberty in the parents and physical examination may provide clues regarding the cause of DP. Delayed onset of puberty is rarely considered a disease in either sex. In fact, DP usually represents a common normal variant in pubertal timing, with favorable outcomes for final height and future reproductive capacity. In adolescents with CDGP, a linear growth delay occurs until immediately before the start of puberty, then the growth rate rapidly increases. Bone age is often delayed. CDGP is a diagnosis of exclusion; therefore, alternative causes of DP should be considered. Functional hypogonadotropic hypogonadism may be observed in patients with transient delay in hypothalamic-pituitary-gonadal axis maturation due to associated conditions including celiac disease, inflammatory bowel diseases, kidney insufficiency, and anorexia nervosa. Permanent hypogonadotropic hypogonadism (pHH) showing low serum value of testosterone or estradiol and blunted follicle-stimulating hormones (FSH) and luteinizing hormones (LH) levels may be due to abnormalities in the central nervous system. Therefore, magnetic resonance imaging is necessary to exclude morphological abnormalities and neoplasia. Moreover, pHH may be isolated, as observed in Kallmann syndrome, or associated with other hormone deficiencies, as found in panhypopituitarism. Baseline or gonadotropin-releasing hormone pituitary stimulated gonadotropin level is not sufficient to easily differentiate CDGP from pHH. Low serum testosterone in male patients and low estradiol values in female patients, associated with high serum FSH and LH levels, suggest a diagnosis of hypergonadotropic hypogonadism. A genetic analysis can reveal a chromosomal abnormality (e.g., Turner syndrome or Klinefelter syndrome). In cases where the adolescent with CDGP is experiencing psychological difficulties, treatment should be recommended.